2006
DOI: 10.2478/s11756-006-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects and modes of action of live yeasts in the rumen

Abstract: Live yeasts (Saccharomyces cerevisiae) are more and more widely used as feed additives for ruminants. They are considered as allochtonous microorganisms in the rumen environment, however, distributed daily to dairy cows or beef cattle they can survive in the digestive tract and interact with autochtonous microbial populations. The positive effects of yeast cells have been mainly demonstrated on growth and activity of fibre-degrading bacteria and fungi, on stabilisation of rumen pH and prevention of lactate acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 57 publications
3
72
0
1
Order By: Relevance
“…Active yeast probably provided better conditions in rumen environment, with stimuli to growth of bacteria responsible for food digestion [3,4,2]. As the interaction between the two factors (active yeast X diets) was not statistically significant it means that the effect of active yeast supplementation was effective on the two diets, independently of their concentrate proportion.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Active yeast probably provided better conditions in rumen environment, with stimuli to growth of bacteria responsible for food digestion [3,4,2]. As the interaction between the two factors (active yeast X diets) was not statistically significant it means that the effect of active yeast supplementation was effective on the two diets, independently of their concentrate proportion.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, besides effects regarding to the better performance of some types of bacteria, [3] pointed the supply of growth factors -vitamins (B complex, para-aminobenzoicacid, etc), dicarboxylic acids (fumarate, malate, etc) and the reduction in protozoa numbers, as possible beneficial effects. [5] concluded that active yeast culture supplementation to finishing lambs fed high energy diets improves weight gain, feed-to-gain ratio and apparent digestibility of DM, OM, CP and NDF, although [6], through meta-analyze of several experiments published from 1990 to 2009, showed that addition of dry active S. cerevisiae yeast to sheep diets had effect for DM, OM and CP apparent digestibility, as well as, for rumen pH and had any effect on growth, feed conversion, ruminal parameters or fiber digestibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rumen allows the development and interactions of a wide variety of microorganisms (Mendes et al, 2012), which are able to adapt to the rumen anaerobic conditions, temperature and pH (Fonty and Chaucheyras-Durand, 2006). In addition, the composition and proportion of ruminal microorganisms are influenced by external factors such as diet, feeding frequency, age (Denman and McSweeney, 2006) and have an important function in feed digestion (Oliveira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Animal response to S. cerevisiae supplementation may be quite variable, and factors such as the nature of the diet, level of productivity, animal physiological and genetic factors and dose and strain of yeast used, among others, may influence the efficacy of this additive (Fonty and Chaucheyras-Durand, 2006). Only studies describing diet composition and malic acid or malate dose were included.…”
Section: Rumenmentioning
confidence: 99%